Private Investment in Urban Regeneration Process: The Case of Golden Horn - Bakbaşa, Ceyda; TÖRE, EVRİM ÖZKAN (My University, 2013)
In this study, the role of private investment in the regeneration process of the Golden Horn is discussed in line with efforts to transform the old industrial zone into a cultural centre. The study points out some important flagship projects for Istanbul and for its surround that exist in Golden Horn. Regarding the urban regeneration understanding in Turkey, which is most commonly based on cultural policies especially in the city centre, the position of private sector investments in Golden Horn seems partial, discontinuous and in a sense, isolated.
Keywords: Culture-led regeneration; Golden Horn; Private investment; Intergovernmental relationship; Istanbul